A Real-Time PCR Method Targeting Camel Ingredient for Food Authentication. (27th November 2019) - Wu, Yajun; Yang, Yange; Wang, Bin; Liu, Mingchang; Han, Jianxun; Chen, Ying
Abstract: The special nutritious value of camel showed high potential for market exploitation. In this paper, a real-time PCR method targeting camel ingredient in camel meat and milk is reported as an approach to fight against adulteration. To understand the impact of processing procedures on the amplifiability of cytb gene, four kinds of processed camel meat were investigated, and the rate of DNA breakage was explored. The method was able to detect 5 fg/μL camel DNA and highly processed food containing 0.01% camel meat with a high confidence level.